2017
DOI: 10.5812/aapm.21740
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Aminophylline in Reducing the Incidence of Acute Kidney Injury After Cardiac Surgery

Abstract: ObjectivesAcute renal failure is a common complication of major cardiovascular surgeries (One-third of patients). Adenosine release as a vascular vasodilator increases after cardiac surgery, which reduces renal and glomerular blood flow and subsequently causes kidney ischemic damage. The present study aimed at evaluating the impact of aminophylline as an adenosine receptor antagonist on renal function after cardiac surgery hoping to find an appropriate method to reduce acute kidney injury.MethodsThe patients i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…However, only three studies compared methylxanthines with a control. Two of these three studies did not use international AKI criteria, and in the remaining study, the incidence of AKI in the control group was significantly higher than that in the intervention group (23.6% vs. 4.2%) ( 155 ). According to RoB 2, this study had some risk of bias.…”
Section: Discussionmentioning
confidence: 99%
“…However, only three studies compared methylxanthines with a control. Two of these three studies did not use international AKI criteria, and in the remaining study, the incidence of AKI in the control group was significantly higher than that in the intervention group (23.6% vs. 4.2%) ( 155 ). According to RoB 2, this study had some risk of bias.…”
Section: Discussionmentioning
confidence: 99%
“…One of the earliest single center double-blinded placebo controlled clinical trials in pediatric patients after CPB did not show significant differences in AKI incidence or difference in secondary clinical outcomes between treatment and control groups (37). Other studies however, have found variable effects, with several reporting improved clinical outcomes and lower incidence of AKI (38, 39).…”
Section: Therapeutic Targetsmentioning
confidence: 99%
“…Cardiac surgery and its complications have negative impacts on kidney function and can lead to acute kidney injury, which is related to augmented complications and mortality (1). Multiple factors, including pre-, intra-, and post-cardiac surgery, make the kidney susceptible to injury, which is known as cardiac surgery-associated acute kidney injury (CSA-AKI) (2). There are more than 30 different diagnostic criteria for CSA-AKI such as RIFLE, KDIGO, AKIN, etc., resulting in different ranges of CSA-AKI incidence, up to 30% in the literature (3).…”
Section: Introductionmentioning
confidence: 99%